The Role of the Military in Guarding Borders in Achieving Global Stability - Ratu Zahirah Lutfie; Al Qadrie, Syarif Redha Fachmi; Uhaib, M. Uhaib; Zhyvko, Zinaida; Salvador, Beatriz Lucia (Cita konsultindo, 2024)
In the contemporary era, borders not only represent geographical barriers between countries but also become central points for maintaining security and stability. This research aims to investigate and analyze the military's role in overcoming growing security challenges along borders, as well as its impact on global stability. The military's role in guarding borders involves a complex set of tasks and responsibilities. Borders are the first line of defense that must be strictly guarded to prevent illegal penetration that could undermine national security. Therefore, military strategies and tactics in securing borders must continue to develop in line with changes in global security dynamics. The main challenges faced by the military in guarding the border include cross-border terrorism, illegal arms trafficking, and regional armed conflict. Terrorism, in particular, has become a global threat that requires a careful response and high levels of coordination between countries. The military, as the front guard in facing this threat, must be able to respond quickly and effectively to maintain regional and global stability. International cooperation is also a key factor in the military's role in protecting borders and global stability. International peace missions and strategic partnerships between countries are important instruments in achieving common goals to maintain security. The military not only functions as a national defense force but also as an agent of global peace and collaboration. Apart from security aspects, the role of the military also has a significant impact on social, economic, and environmental dimensions. Military presence along borders can influence the social and cultural structure of local communities. Therefore, this research will examine the social impacts of military presence, including their interactions with local communities and their impact on social identity. From an economic perspective, the military has the potential to contribute to economic development in border areas. Natural resources are also an important part of the military's role in protecting borders. Border areas are often rich in strategic natural resources. Therefore, the military also has a responsibility to protect and manage these natural resources so that they are not exploited illegally, as well as ensure the sustainability of their use. In the context of international law, the military's role in guarding borders must be within the framework of compliance with legal norms and respect for human rights. This study will evaluate the extent to which the military complies with international law and operates by humanitarian principles. Through an in-depth analysis of these aspects, this research is expected to provide holistic and in-depth insight into the military's role in protecting borders and global stability.